Innovation and the export performance of firms in transition economies: the relevance of the business environment and the stage of transition. (17th December 2019) - Reçica, Fisnik; Hashi, Iraj; Jackson, Ian; Krasniqi, Besnik A.
This paper investigates the impact of product and process innovation on firms' export performance in transition economies (TEs) which embarked on a systemic change from a planned to a market economy in the early 1990s. The research builds on the technology gap theory and the analysis of the self-selection of firms into the export market. Unlike other studies that have focused on the export behaviour of firs in developed economies where business environment is generally stable and favourable, the paper controls for the relevance of business environment and the stage of transition on export performance of firms. The paper uses the firm-level Business Environment and Performance Survey data undertaken by the European Bank for Reconstuction and Development in 2002, 2005 and 2008 in 29 TEs. Findings show that the impact of innovation on export performance increases with the transition reforms. Macroeconomic instability acts as a moderating factor of export performance in countries at high transition stage, as it pushes firms to export more, as a risk shifting echanism. The main implication of the study is that the impact of some explanatory factors on export performance differs through the stages of transition.